2019
DOI: 10.3201/eid2502.181286
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus IgM Detection and Neutralizing Antibody Profiles 12–19 Months after Illness Onset

Abstract: Data on the duration of detectable Zika virus–specific IgM in infected persons are limited. Neutralizing antibody cross-reactivity occurs between Zika virus and related flaviviruses, but the degree to which this confounds diagnosis is uncertain. We tested serum specimens collected 12–19 months after illness onset from patients with confirmed Zika virus disease for Zika virus IgM and Zika virus and dengue virus neutralizing antibodies. Among 62 participants, 45 (73%) had detectable Zika virus IgM and 12 (19%) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 20 publications
1
36
0
1
Order By: Relevance
“…In one study of patients with symptomatic Zika virus infection, 87% (52 of 60) had detectable IgM antibodies >60 days after symptom onset (5). In another cohort study of persons with confirmed Zika virus infection, 73% (45 of 62) had detectable IgM antibodies at 12-19 months after acute illness (51). Data for closely related flaviviruses (i.e., West Nile and yellow fever viruses) indicate that IgM antibodies might be detectable in serum for months or years after initial infection (9)(10)(11).…”
Section: Dengue and Zika Virus Infections And Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…In one study of patients with symptomatic Zika virus infection, 87% (52 of 60) had detectable IgM antibodies >60 days after symptom onset (5). In another cohort study of persons with confirmed Zika virus infection, 73% (45 of 62) had detectable IgM antibodies at 12-19 months after acute illness (51). Data for closely related flaviviruses (i.e., West Nile and yellow fever viruses) indicate that IgM antibodies might be detectable in serum for months or years after initial infection (9)(10)(11).…”
Section: Dengue and Zika Virus Infections And Immune Responsementioning
confidence: 99%
“…Recent findings indicate that neutralizing antibody titers might be able to differentiate dengue and Zika virus infections, particularly in specimens collected ≥3 months after illness onset (66). However, at 12-19 months after confirmed Zika virus infection, 17 (27%) of 62 persons in Florida still had neutralizing antibody titers that could not distinguish between dengue and Zika viruses (51). On the basis of previous flavivirus research and limited data specific to dengue and Zika viruses, the historic use of a four-fold higher titer by PRNT might not discriminate between dengue and Zika virus antibodies during the acute illness, especially following secondary flavivirus infections (8,56,57,66).…”
Section: Dengue and Zika Virus Diagnostic Testingmentioning
confidence: 99%
“…Using a neutralization assay to test paired sera collected in Fiji, we found that the mean change in neutralizing antibody titres against Figure 3), although the pattern is not conclusive since there is a lack of power to analyze this relationship due to the small number of available samples tested. To our knowledge, the only other study that investigated the longterm persistence of neutralizing antibodies against ZIKV was conducted in 62 residents of Miami (Florida, USA), who had a confirmed ZIKV infection in 2016 17 .…”
Section: Discussionmentioning
confidence: 99%
“…If so, the high level of seroprevalence in affected countries may provide herd immunity such that the current ZIKV epidemic is over in many locations and the virus will not be able to re-emerge for decades to come 2,9,13,15 . Recent evidence suggests that neutralizing antibodies can distinguish between ZIKV and dengue virus (DENV) -a closely related Flavivirus -and that the immune response following ZIKV infection can persist over a year 16,17 . Early data also suggests that primary ZIKV infection confers protective immunity 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Anti-WNV IgM could still be detected even after 8 year (7), and immune response to YFV vaccine arouse long term IgM presence (6). Recently, anti-ZIKV IgM and neutralizing antibodies were detected in sera up to 19 months after infection (13).…”
Section: Discussionmentioning
confidence: 99%